Anatomical classification of advanced biliary tract cancer predicts programmed cell death protein 1 blockade efficacy - Huang, Lingli; Wang, Fang; Wang, Fenghua; Jiang, Qi; Huang, Jinsheng; Li, Xujia; Guo, Guifang (Frontiers in Pharmacology, 2024)
Background Immune checkpoint blockade (ICB)-based immunotherapy brought new hope for advanced biliary tract cancer (BTC) treatment, however, there was no study primarily focusing on if different anatomical types of unresectable BTC reacted differently to ICB.2 Methods We retrospectively collected the data of advanced biliary tract cancer patients with anti-programmed cell death protein 1 (anti-PD1) therapy from two affiliated hospitals of Sun Yat-Sen university. The effects of anti-PD1 were compared among different anatomical sites. GSE32225 and GSE132305 datasets were used to further analyze the differences in immune microenvironment between the intrahepatic cholangiocarcinoma (ICC) and extrahepatic cholangiocarcinoma (ECC).Results A total of 198 advanced BTC patients were enrolled, consisting of 142 with ICC and 56 with Others(including extrahepatic cholangiocarcinoma and gallbladder cancer). In anti-PD1 treated patients, the ICC group (n = 90) achieved longer median progression-free survival (mPFS) (9.5 vs 6.2 months, p=0.02) and median overall survival (mOS) (15.1 vs 10.7 months, p=0.02) than the Others group (n=26).However, chemotherapy didn't show different effect between two groups (mOS 10.6 vs 12.1 months, p=0.20; mPFS 4.9 vs 5.7 months, p = 0.83). In the first-line anti-PD1, the ICC group (n = 70) achieved longer mOS (16.0 vs 11.8 months, p=0.04) than the Others group (n=19). Moreover, most chemokines, chemokine receptors, MHC molecules, immunostimulators and immunoinhibitors in ICC were stronger than those in ECC. CD8+T cells and Macrophage M1 were higher in ICC than ECC in most algorithms. Immune differential genes were mainly enriched in antigen processing and presentation and cytokine receptors.Our study showed that the efficacy of anti-PD1 was greater in ICC than in other BTC. The difference of immune-related molecules and cells between ICC and ECC indicated ICC could benefit more from immunotherapy.